Ultrastructural Evidence of Mitochondrial Dysfunction in Osteomyelitis Patients - Mendelsohn, Daniel H.; Niedermair, Tanja; Walter, Nike; Alt, Volker; Rupp, Markus; Brochhausen, Christoph (International journal of molecular sciences, 2023)
Osteomyelitis is a difficult-to-treat disease with high chronification rates. First studies suggest increases in mitochondrial fission and mitochondrial dysfunction as possible contributors to the accumulation of intracellular reactive oxygen species and thereby to the cell death of infected bone cells. The aim of the present study is to analyze the ultrastructural impact of bacterial infection on osteocytic and osteoblastic mitochondria. Human infected bone tissue samples were visualized via light microscopy and transmission electron microscopy. Osteoblasts, osteocytes and their mitochondria were analyzed histomorphometrically and compared with the control group of noninfectious human bone tissue samples. The results depicted swollen hydropic mitochondria including depleted cristae and a decrease in matrix density in the infected samples. Furthermore, perinuclear clustering of mitochondria could also be observed regularly. Additionally, increases in relative mitochondrial area and number were found as a correlate for increased mitochondrial fission. In conclusion, mitochondrial morphology is altered during osteomyelitis in a comparable way to mitochondria from hypoxic tissues. This gives new perspectives on the treatment strategies since the manipulation of mitochondrial dynamics may improve bone cell survival as a potential new target for the therapy of osteomyelitis.